Low-Cost Automotive Capacitive Discharge Ignition (CDI) Coil for Low Frequency Ozone Generator - Muhammad Ikhsan Sani (JURNAL INFOTEL, 2019)
This paper presents an alternative solution for generating ozone using a low-cost automotive Capacitive Discharge Ignition (CDI) coil. High voltage ozone generating theory is implemented using a capacitive discharge circuit that uses ignition coil as its high voltage step-up transformer. A computer simulation has been performed to confirm the validity of the circuit function. By calculation and measurement, the coil has 196,71 voltage amplification factor. Furthermore, it has been implemented at a low frequency of about 10 - 40 Hz. Meanwhile, ozone output is measured using the colorimetric method. From a series of tests, that coil implementation has successfully generated a high voltage on ozone reactor tube at 31.47 kV voltages that essential for ozone production. Change of frequency will change the ozone concentration output linearly. The test was conducted using three different frequency: 10 Hz, 20 Hz, and 40 Hz. The result has shown that the highest ozone yield was 80 mg/hour.